Description of Health Knowledge and Healthy Lifestyle of Elementary School Students - Feri Agustiawan; Dwi Karti (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: The purpose of this study was to determine the health knowledge and healthy lifestyles of elementary school students. Methodology: This study is a descriptive study using a survey method with instruments in the form of measurement tests, questionnaire instruments to measure health knowledge and healthy lifestyles. The subjects of the study were 52 students of grade V and VI of Baratan State Elementary School, Pakem District, Sleman Regency. Descriptive data analysis techniques with percentages. Main Findings: The health knowledge of students in grades V and VI of Baratan State Elementary School, Pakem District, Sleman Regency is sufficient with a percentage of 36.5% and the students' healthy lifestyle is moderate with a percentage of 50.0%. Novelty/Originality of this study: These findings can be the basis for developing health education programs that are more focused on establishing healthy lifestyles, especially at the elementary school level, which has not been widely discussed in the local context.